Focus on composing photos - Ensenberger, Peter (Focus on series., 2011)
As digital cameras and software packages become more advanced, seemingly by the minute, it has become easier than ever to overlook the basic elements which have always resulted in the best photographs, no matter how fancy (or primitive) the camera itself. Composition is the single most important aspect of creating great images, no matter what level of photographer you happen to be. No amount of digital wizardry can turn a badly composed image into a picture you would want to display. While many books on composition tend to overcomplicate the subject, this book breaks down everything you need to know into small, digestible chunks of information that you will actually remember once you're out and about taking pictures. Instead of plodding through long and complex pages of text, this book supplements the necessary information, such as the basics of the rule of thirds and how to get good highlights and shadows, with tons of gorgeous, full color images that actually show you what to do and how to do it, rather than just telling you what to try. You'll be amazed at the gorgeous images you'll create, whether your passion is for photographing your family, pets, travel adventures, nature, or anything else. *Beautiful design with full color images on every page which makes it much easier to remember everything you've learned once you're behind the camera *Tip boxes spread throughout the book highlight the most essential information so you can get started right away making better images *Each chapter contains an easy-to-follow assignment to jumpstart your own creativity.